Csr In Emerging Markets: Challenges And Opportunities For Shell Companies - Yohana Natalia Cristanti; Nathalie Elshaday; Hwihanus (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This article explores the challenges and opportunities of Corporate Social Responsibility (CSR) in emerging markets, focusing on a case study of a Shell company. Emerging markets present unique dynamics that affect the implementation and effectiveness of CSR. Shell, as one of the world's largest energy companies, has operated in various emerging markets and sought to implement effective CSR practices. Through an in-depth analysis of Shell's operations in these markets, this article identifies key factors that influence CSR success and provides recommendations for best practices. It finds that while there are significant challenges related to local regulations, infrastructure and culture, there are great opportunities to increase CSR impact through collaboration with local stakeholders, technological innovation and local capacity building. The article concludes that adaptation and flexibility are key for multinational companies like Shell to face the challenges and capitalize on the opportunities of CSR in emerging markets.